Costs and effects of abdominal versus laparoscopic hysterectomy: systematic review of controlled trials. - Claudia B M Bijen (PLoS ONE, 2009)
OBJECTIVE: Comparative evaluation of costs and effects of laparoscopic hysterectomy (LH) and abdominal hysterectomy (AH). DATA SOURCES: Controlled trials from Cochrane Central register of controlled trials, Medline, Embase and prospective trial registers. SELECTION OF STUDIES: Twelve (randomized) controlled studies including the search terms costs, laparoscopy, laparotomy and hysterectomy were identified. METHODS: The type of cost analysis, perspective of cost analyses and separate cost components were assessed. The direct and indirect costs were extracted from the original studies. For the cost estimation, hospital stay and procedure costs were selected as most important cost drivers. As main outcome the major complication rate was taken. FINDINGS: Analysis was performed on 2226 patients, of which 1013 (45.5%) in the LH group and 1213 (54.5%) in the AH group. Five studies scored > or =10 points (out of 19) for methodological quality. The reported total direct costs in the LH group ($63,997) were 6.1% higher than the AH group ($60,114). The reported total indirect costs of the LH group ($1,609) were half of the total indirect in the AH group ($3,139). The estimated mean major complication rate in the LH group (14.3%) was lower than in the AH group (15.9%). The estimated total costs in the LH group were $3,884 versus $3,312 in the AH group. The incremental costs for reducing one patient with major complication(s) in the LH group compared to the AH group was $35,750. CONCLUSIONS: The shorter hospital stay in the LH group compensates for the increased procedure costs, with less morbidity. LH points in the direction of cost effectiveness, however further research is warranted with a broader costs perspective including long term effects as societal benefit, quality of life and survival.